2000
DOI: 10.1038/sj.onc.1203917
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the human osteopontin promoter: functional analysis and DNA-protein interactions

Abstract: Synthesis of cell attachment proteins and cytokines, such as osteopontin (OPN), can promote tumor cell remodeling of the extracellular matrix into an environment that promotes tumor cell attachment and migration. We investigated the transcriptional regulation of OPN in the U-251MG and U-87MG human malignant astrocytoma cell lines. Deletion and mutagenesis analyses of the OPN promoter region identi®ed a proximal promoter element (724 to 794 relative to the transcription initiation site) that is essential for ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 34 publications
2
46
0
Order By: Relevance
“…The first one, located at Ϫ106 on the rat OPN promoter, is associated with SMC differentiation (24) and glucose signaling (42) and is conserved in the mouse and human promoter, although its function has not been demonstrated in these species. A second Ebox, located at Ϫ81 in the mouse promoter (25) and at Ϫ84 in the human promoter (43), was also shown to be involved in glucose signaling (25). According to our data, none of these sites are involved in UTP-induced OPN expression.…”
Section: Discussionmentioning
confidence: 85%
“…The first one, located at Ϫ106 on the rat OPN promoter, is associated with SMC differentiation (24) and glucose signaling (42) and is conserved in the mouse and human promoter, although its function has not been demonstrated in these species. A second Ebox, located at Ϫ81 in the mouse promoter (25) and at Ϫ84 in the human promoter (43), was also shown to be involved in glucose signaling (25). According to our data, none of these sites are involved in UTP-induced OPN expression.…”
Section: Discussionmentioning
confidence: 85%
“…2A and B, a series of factors were secreted and increased in CM* compared with the control medium. Many of these factors were associated with tumor cell malignant phenotype, including chemotherapy resistance and tumor progression, migration and invasion (27)(28)(29). CCL5 was significantly increased up to ~72-fold compared with the control medium.…”
Section: Ccl5 Is Strongly Secreted From Cafs After Cisplatin Treatmentmentioning
confidence: 94%
“…The SNP at Ϫ66 was predicted to bind the SP1 transcription factor both by the knowledge that the sequence between Ϫ68 and Ϫ59 is an SP1 binding site in the human OPN promoter (39) and by promoter analysis with the MatInspector software. This was confirmed by our EMSA in which we showed that SP1 and SP3 factors recognize this site and that the allele with the T nucleotide inside the SP1 recognition sequence has a higher binding affinity.…”
Section: Discussionmentioning
confidence: 99%